Surahi mein samundar Gazle aur nazme - Chintan,Shubh (India notion press, 2021)
This book contains 101 gazals and poems, in which a myriad of human emotions have been painted be it love, hate, anger, revolt, helplessness and jealousy. It is an attempt to fill an entire ocean of life in a pot of gazals. The readers will find gazals on patriotism, Bharat, dil (heart), khuda (God), mother, father, brother, rain, clouds, space, moon, Taj Mahal, Chandni and what not.
Keywords: IRS; Customs and indirect taxes